2010
DOI: 10.1097/ta.0b013e3181e6138a
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Mortality: The Relationship With Associated Injuries and Fracture Treatment Methods in Patients With Unilateral or Bilateral Femoral Shaft Fractures

Abstract: The increase in mortality with BFs is more closely associated with the presence of associated injuries and poor physiologic parameters than with the presence of the BF alone. The presence of BFs should alert the clinician to the very high likelihood (80%) of significant associated injuries in other body systems and their life-threatening potential. Damage control fixation options should be considered in the subgroup with a very high New Injury Severity Score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 22 publications
2
33
0
2
Order By: Relevance
“…It may be that patients who survive the early stresses of high-energy trauma have enough physiologic reserve to survive after hospital discharge. The association of mortality with ISS and age was seen in our study and has been confirmed in other studies [4,6,12,27]. The cumulative injuries, that is, the ISS and influence of physiologic reserve may play a greater role in mortality for this group of patients rather than the presence of a high-energy femur fracture.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It may be that patients who survive the early stresses of high-energy trauma have enough physiologic reserve to survive after hospital discharge. The association of mortality with ISS and age was seen in our study and has been confirmed in other studies [4,6,12,27]. The cumulative injuries, that is, the ISS and influence of physiologic reserve may play a greater role in mortality for this group of patients rather than the presence of a high-energy femur fracture.…”
Section: Discussionsupporting
confidence: 77%
“…Approximately 10% of patients in this group did not have orthopaedic surgery secondary to death in an emergency department or death during or after initial general surgery intervention, and one patient who was nonambulatory refused surgery. Low-energy femur fractures have been studied extensively in the elderly population [3,4,[22][23][24]27]. However, the impact of high-energy femur fractures in elderly patients with trauma has not been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 94%
“…Сочетание перелома бедренной кости, в особеннос-ти билатерального, с множественными переломами ребер и повреждениями внутренних органов груди с гемо-и пневмотораксом существенно увеличивает кровопотерю и шокогенность политравмы, повышает вероятность раннего смертельного исхода [7][8][9].…”
Section: патофизиология взаимного отягощения скелетных и торакальных unclassified
“…Однако при сравнении летальности в группах боль-ных, сопоставимых по тяжести политравмы по шкале ISS, не выявлено преимущества тактики DCO перед ETC в лечении билатеральных переломов бедренной кости [60]. Но все же при тяжести политравмы по шкале NISS более 40 баллов следование тактике DCO в лечении билатеральных переломов бедренной кости сопровождалось наименьшей летальностью [9].…”
Section: стратегия «безопасного окончательного остеосинтеза» при полиunclassified
“…In particular, bilateral femur fractures result from high-velocity impacts, leading to complex fractures and severe injuries of the surrounding soft tissue envelope [35]. These injuries are characterized by high blood loss [6], severe generalized autodestructive inflammation [16], and remote organ damage [6,16,28].…”
Section: Introductionmentioning
confidence: 99%